Dlaczego nauka krytycznego korzystania z informacji jest równie ważna jak nauka czytania i pisania – przemiany alfabetyzacji w edukacji wczesnoszkolnej - Mironiuk, Alicja (Studia Edukacyjne, 2024)
According to a popular belief, students of early childhood education “only read, write and count”, continuing the literacy process that began in kindergarten. In my article, I emphasize the importance of another dimension of literacy. i.e. digital literacy, and more precisely, information literacy, which is an important part of it. Identifying sources of information; recognizing the mechanisms governing the distribution of information on the Internet (social media); distinguishing facts from fake news and opinions; safe use of digital media; awareness and respect for copyright are some of the major aspects of information literacy. Consequently, information literacy and media education constitute the proverbial ABC of modern students.